Integration of Standard Operating Procedures for Waste Management and Ecotheological Education as a Strategic Solution for Saving the Sacred Environment - Ni Nyoman Sutrisna Yanti (JURNAL ILMIAH GEMA PERENCANA, 2026)
Sacred areas in Bali currently face a serious threat of ecosystem degradation due to the escalating volume of unmanaged ritual waste, where the dominance of non-organic materials has polluted the soil and water sources. This policy article aims to formulate a strategy to save the sacred environment through the integration of Standard Operating Procedures (SOPs) for waste management and strengthening ecotheology education. The policy methodology used in this study is a qualitative-descriptive approach with the William N. Dunn model of policy analysis techniques, which evaluates various alternative solutions based on the criteria of effectiveness, efficiency, adequacy, equity, responsiveness, and technical feasibility. Through in-depth problem identification, it was found that the root of the problem lies in weak technical regulations and the absence of a waste sorting mechanism based on spiritual values ​​​​in religious authorities. The results of the scoring analysis indicate that regulatory intervention through the issuance of a Circular Letter on the Curriculum Guidelines for Ecotheology Extension is the most strategic solution. This policy is expected to be able to recommend standardization of ceremonial materials and the provision of independent sorting infrastructure in each sacred area. The implementation of this policy is expected to transform ritual waste management from a linear to a circular model, while simultaneously restoring the essence of sacred areas as centers of ecological harmony, in accordance with the Tri Hita Karana philosophy. With a mandatory legal framework, religious authorities can assume a green leadership role in sustainably mitigating environmental crises at the grassroots level.